2023
DOI: 10.1287/orsc.2022.1595
|View full text |Cite
|
Sign up to set email alerts
|

Just Diverse Among Themselves: How Does Negative Performance Feedback Affect Boards’ Expertise vs. Ascriptive Diversity?

Abstract: We investigate how negative performance feedback affects board diversity, which is instrumental in shaping a firm’s strategic change. When a firm underperforms compared with its aspiration, its board is motivated to promptly address the underperformance. The board needs to not only help search for strategic alternatives but also quickly build consensus around its strategic reorientation. These two motivations lead the board to value two dimensions of diversity among its members differently. On the one hand, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 114 publications
0
5
0
Order By: Relevance
“…It has been long shown that firms change their strategies after performance changes. For example, Jung et al (2022) find that low-performing firms are more likely to increase board expertise diversity. Vidal and Mitchell (2015) argue that high-performing firms tend to use divestures to slack resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has been long shown that firms change their strategies after performance changes. For example, Jung et al (2022) find that low-performing firms are more likely to increase board expertise diversity. Vidal and Mitchell (2015) argue that high-performing firms tend to use divestures to slack resources.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the desire to seek solutions encourages decision-makers to initiate certain changes and to undertake potentially higher risks associated with the search or change (Bromiley, 1991; Lant et al, 1992). Indeed, the search will inevitably require changes in certain issues identified as potential sources of the performance shortfalls and introduce the risk of failing to fulfill the desired benefits or even engendering additional losses (Jung et al, 2022; Posen et al, 2018).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…decisions with both potential benefits and downsides), including board diversity (e.g. Jung et al, 2022), corporate social responsibility (e.g. Smulowitz et al, 2020; Wang et al, 2021), financial misconduct (e.g.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations